2010
DOI: 10.1111/j.1365-2621.2010.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal processing on oxide reductase inactivation and on colour fixing in erva‐mate (Ilex paraguariensis St. Hill) leaves

Abstract: Leaves of erva-mate (Ilex paraguariensis St. Hill) were heat treated with different combinations of time and temperature. Polyphenol oxidase (PPO) and peroxidase (POD) residual activities and colouring (L, a, b and DE) were studied after treatment for 3 weeks. The best results for enzyme inactivation after heat treatment were obtained with the leaves treated at 450°C for 15 s and at 500°C for 10 s, with reductions of 90.6% and 83.4% for PPO and 94.5% and 92.7% for POD. These groups also showed low levels of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…There are few studies on thermal inactivation of POD and PPO enzymes in mate leaves (Ceni et al, 2009;Provesi et al, 2010;Xander, Acosta, Scipioni, & Argüello, 2000) and none on the kinetics of the inactivation of these enzymes in the plant matrix of mate, as performed in this study. This raw material has irregularities in its dimensions which should be considered for future industrial projects.…”
Section: Cytamentioning
confidence: 81%
See 3 more Smart Citations
“…There are few studies on thermal inactivation of POD and PPO enzymes in mate leaves (Ceni et al, 2009;Provesi et al, 2010;Xander, Acosta, Scipioni, & Argüello, 2000) and none on the kinetics of the inactivation of these enzymes in the plant matrix of mate, as performed in this study. This raw material has irregularities in its dimensions which should be considered for future industrial projects.…”
Section: Cytamentioning
confidence: 81%
“…These results with temperatures lower than those in the traditional industrial processing show that the inactivation of PPO enzymes does not justify the use of excessive heat, commonly adopted in mate factories. Provesi et al (2010) evaluated the thermal treatment of mate leaves in an oven and reported that, after thermal treatment, PPO enzymes showed higher residual activity than POD enzymes. However, only POD showed recovery of enzyme activity after seven days of storage (Whitaker, Voragen, & Wong, 2003).…”
Section: Definition Of the Time/temperature Binomialmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mate processing is done in factories at a high temperature, the sapeco operation at mild temperature was studied by Provesi and others () and Nabechima (), and it was found that 255 °C was sufficient for the process, and that it inactivated oxidoreductase enzymes.…”
Section: Introductionmentioning
confidence: 99%